Perilaku Masyarakat Dan Indeks Entomologi Vektor Demam Berdarah Dengue Di Kota Cimahi - Firda Yanuar Pradani; M. Ezza Azmi Fuadiyah; yuneu yuliasih (Loka Litbang Kesehatan Pangandaran, 2010)
Dengue haemorhagic fever (DHF) was one of most dangerous disease in Indonesia. The number of case showed increased year by year since first time observed. Vector control that used by government always using Insecticides. A continuity of it cancaused resistances of mosquito, and it will be more dangerous.In District Cimahi, vector control doing by mosquitoes habitat eradication (PSN) for last 3 years. It done by invite people to participate to make environment clean. Every week, peopleon duty going house to house to check water container condition. They also give support and suggest how to prevent breeding mosquitoes to people. The aim of this research is to evaluate knowledge, practice and attitude people about DBD and to count Entomology Index in district Cimahi. This research observe that globally people attitude is good, knowledge is middle and practicestill bad. Larvae Free Index (Angka Bebas Jentik) when observe show that in Cibabat first week still below national Larvae Free Index. In Pasirkaliki, first week and second week Larvae Free Index below national Larvae Free Index.